In vitro cultivation and regeneration of Solanum melongena (L.) using stem, root and leaf explants - Ray, Bishnu Pada; Hassan, Lutful; Sarker, Smreeti Kana (Nepal Journal of Biotechnology, 2010)
The treatment combinations was BAP (0, 2.0, 3.0 and 4.0 mg/L) and NAA (0, 0.1, 0.5, and 1.0 mg/L). The rate of callus formation varied in different treatments. The highest amount of callus (48.66%) was produced on MS medium containing 2.0 mg/l BAP and 0.5 mg/l NAA from stem and 8.2 days required for callus induction. The number of shoot regenerated through callus from stem containing 2.0 mg/l BAP and 0.5 mg/l NAA was 3.4 (23.287%) and days required for 38.8 days. Key words: Regeneration; BAP; NAA. Nepal Journal of Biotechnology. Jan. 2011, Vol. 1, No. 1 : 49-54